1999
DOI: 10.1016/s0735-1097(99)00452-0
|View full text |Cite
|
Sign up to set email alerts
|

Complications of endomyocardial biopsy in children

Abstract: Risk of endomyocardial biopsy is highest in sick children with suspected myocarditis on inotropic support. However, EMB can be performed safely with very low morbidity in pediatric heart transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
114
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(120 citation statements)
references
References 14 publications
2
114
1
3
Order By: Relevance
“…In a review of 1,000 endomyocardial biopsy procedures, the incidence of this complication was 0.9%. 29 The ACC/AHA guidelines for the treatment of heart failure include endomyocardial biopsy as a Class IIb recommendation. In any type of MC, endomyocardial biopsy is quite informative for making an accurate diagnosis, in assessing the use of anti-inflammatory agents, and in predicting prognosis.…”
Section: Myocardial Biomarkersmentioning
confidence: 99%
“…In a review of 1,000 endomyocardial biopsy procedures, the incidence of this complication was 0.9%. 29 The ACC/AHA guidelines for the treatment of heart failure include endomyocardial biopsy as a Class IIb recommendation. In any type of MC, endomyocardial biopsy is quite informative for making an accurate diagnosis, in assessing the use of anti-inflammatory agents, and in predicting prognosis.…”
Section: Myocardial Biomarkersmentioning
confidence: 99%
“…Although endomyocardial biopsy in acute myocarditis is relatively safe with experienced providers, accurate interpretation remains a challenge, and there is a risk of arrhythmia, right ventricular perforation, and tamponade. 16 On univariable analysis, MRI was associated with lower mortality/transplantation and endomyocardial biopsy with higher mortality/transplantation; however, there was a lack of independent association. Several factors, including the severity of a patient's condition, might impact the decision to perform these tests and hence this finding.…”
mentioning
confidence: 96%
“…Of these only two have received class I recommendation for EMB (Table). In a retrospective review analyzing the morbidity and mortality of EMB in children, highest risk was found in children with suspected myocarditis on inotropic support (Pophal et al, 1999). Authors also found that risk of biopsy in small children (< 10 kg) or sick infants was extreme.…”
Section: Biopsymentioning
confidence: 99%
“…Several issues have to be considered before making a decision about biopsy. As stated earlier, some complications such as pneumothorax, dysrhythmia, perforation and death, may occur during the procedure, and it can be hazardous for particularly pediatric patients (Pophal et al, 1999). Limited sensitivity of EMB that is related with sampling error should also be evaluated (Hauck et al, 1989).…”
Section: Biopsymentioning
confidence: 99%